An efficient self-certified multi-proxy signature scheme based on elliptic curve discrete logarithm problem - Tahat, Nedal; Alomari, A. K.; Al-Hazaimeh, Obaida M.; Al-Jamal, Mohammad F. (Journal of discrete mathematical sciences & cryptography, 2020)
Multi-proxy signature schemes (MPSS) allow n proxy signers to generate a valid signature on behalf of the original signer. A new efficient self-certified MPSS with message recovery based on the Elliptic Curve Discrete Logarithm Problem (i.e., ECDLP) is proposed in this paper. A rationale for proposing a new scheme is to improve the verification process performance by combining the verification process with message recovery in one single stage (i.e., simultaneously). The security and performance analysis shows, the new scheme has many advantages over the traditional MPS schemes. These benefits include decreasing costs (i.e., certificate sizes, consumption time, and bandwidth requirements) and increasing speed.